SOCIO-ECONOMIC CHARACTERISTICS OF MICROFINANCE BENEFICIARIES IN GHANA – EVIDENCE FROM SINAPI ABA TRUST MICROFINANCE INSTITUTION - Antoh, Ernestina Fredua; Enu-Kwesi, Francis; Addison, Monica (Archives of Business Research, 2015)
The paper offers empirical authenticationof the assumption that microfinance beneficiaries are generally characterized by certain socio-economic attributes with evidence from the Sinapi Aba Trust (SAT) microfinance beneficiaries. Data were gathered from 361 randomly sampled beneficiaries using a mixed method design and cross-sectional survey approach, with a focus on the social and economic profiles of respondents. Descriptive analysis was used to present the socio-demographic and economic characteristics.The results support the common assumption that microfinance beneficiaries comprise mainly low income women engaged in informal activities. Largely, the beneficiaries were economically active, with basic level education, mostly married, and a bigger percentage had been on SAT program for up to five years. Their businesses were predominated by retail trade, small-scale manufacturing, services, food and agriculture, all of which generally required smaller start-up capital, and their sources of start-up funds were mainly from individual or family savings. The paper recommends the documentation of baseline characteristics of beneficiaries by microfinance institutions to facilitate trend and transformation analysis.Si